Erosion defect formation in Ni-gate AlGaN/GaN high electron mobility transistors. (March 2017) - Whiting, P.G.; Holzworth, M.R.; Lind, A.G.; Pearton, S.J.; Jones, K.S.; Liu, L.; Kang, T.S.; Ren, F.; Xin, Y.
Abstract: High electron mobility transistors based on Aluminum Gallium Nitride/Gallium Nitride heterostructures are poised to become the technology of choice for a wide variety of high frequency and high power applications. Their reliability in the field, particularly the reliability of the gate electrode under high reverse bias, remains an ongoing concern, however. Rapid increases in gate leakage current have been observed in devices which have undergone off-state stressing. Scanning Electron Microscopy, scanning probe microscopy, and Transmission Electron Microscopy have been used to evaluate physical changes to the structure of Ni-gated devices as the gate leakage current begins its initial increase. This evaluation indicates the formation of an interfacial defect similar to erosion under the gate observed by other authors. Defect formation appears to be dependent upon electrical field as well as temperature. Transmission Electron Microscopy has been used to demonstrate that a chemical change to the interfacial oxynitride layer present between the semiconductor and gate metal appears to occur during the formation of this defect. The interfacial layer under the gate contact transitions from a mixed oxynitride comprised of gallium and aluminum to an aluminum oxide. Highlights: Off-state stepped stressing was performed on Ni-gate AlGaN/GaN HEMTs. The formation of an interfacial defect similar to erosion under the gate has been observed. The defect is 2.8 nm thick and results in the consumption 1.3 nm of AlGaN under the gate. Defect formation appears to be dependent upon electrical field as well as temperature. TEM shows AlON at the AlGaN/Ni-Gate interface converts to AlO during defect formation.